البنية التحتية الرقمية ودورها في جذب الإستثمار الأجنبي المباشر إلى الجزائر خلال الفترة ) 2019 _ 2022 ): Digital infrastructure and its role in attracting foreign direct investment to Algeria during the period (2019_2022) - بلغنو سومية; مواسيم رميساء نجاة (Journal of North African Economies, 2025)
The study aims to shed light on the reality of digital infrastructure in Algeria, and its role in attracting and enhancing foreign investments in the country. This is done by presenting the most important indicators of information and communication technology, as well as the reality of Algeria in the field of using modern technology, and the most important challenges it faces. The study concluded with a set of results and recommendations, most notably that the digital infrastructure in Algeria is very weak and must be developed and strengthened, as a result of its crucial role in attracting foreign direct investment.